Micro-structural and tribological assessment of HVOF sprayed coating by Co alterations for wear applications. (12th June 2019) - Sharma, Mithlesh; Goyal, Deepak Kumar; Kaushal, Gagandeep
Abstract: This paper illustrates the slurry erosion behavior by evaluating three operating process parameters, such as slurry concentration, impact velocity and impact angle of High velocity Oxy Fuel (HVOF)-sprayed WC-17Co and WC-12Co coating on substrates of AISI304 turbine steel. The experiments were structured using Taguchi L9 design matrix on a self fabricated erosion test rig. The output parameter in terms of erosion loss is measured from thermo-gravimetric analysis. The erosion mechanism of uncoated and coated steel was further analyzed through Scanning Electron microscope (SEM) and X-ray Diffraction analysis (XRD). It has been observed that uncoated steel degraded severely due to pitting and ploughing action of the erodent particles. However erosion reduced appreciably by 53% after the application of the HVOF-sprayed WC-12Co coating and was further improved by 4% via HVOF-sprayed WC-17Co coating. Some losses on the surface of both coated steels were attributed by the presence of splat, minor ploughing and micro-chipping. Slurry concentration followed by impact velocity was acknowledged as critical parameters of the study.